The Influence of Sevelamer Hydrochloride and Calcium Carbonate on Markers of Inflammation and Oxidative Stress in Hemodialysis at Six Months of Follow-Up - Díaz-De la Cruz, Elodia Nataly; Cerrillos-Gutiérrez, José Ignacio; García-Sánchez, Andrés; Prado-Nevárez, Carlos Gerardo; Andrade-Sierra, Jorge; Jalomo-Martínez, Basilio; Banda-López, Adriana; Rojas-Campos, Enrique; Miranda-Díaz, Alejandra Guillermina (Frontiers in Medicine, 2021)
Patients with end-stage renal disease (ESRD) present alterations in mineral and bone metabolism. Hyperphosphatemia in ESRD is considered an independent risk factor for cardiovascular disease (CVD), increasing morbidity, and mortality. Sevelamer hydrochloride is a calcium-free, non-absorbable phosphate-chelating polymer. Calcium carbonate chelator is helpful in controlling serum phosphate levels. There is insufficient information on the influence of sevelamer hydrochloride and calcium carbonate on the behavior of oxidative stress (OS) markers and inflammation in patients on hemodialysis (HD). A randomized open clinical trial was carried out on patients to evaluate sevelamer hydrochloride and calcium carbonate influence at 6 months of study follow-up. Levels of oxidants (LPO, NO, and 8-isoprostanes), antioxidants (SOD and TAC), oxidative DNA damage (8-OHdG and hOGG1), pro-inflammatory cytokines (IL-6 and TNF-α), and inflammation markers (ferritin and C-reactive protein) were measured with colorimetric and ELISA methods. We found a significant increase in oxidants LPO and NO, and antioxidants SOD and TAC, and downregulation of IL-6 and TNF-α. Ferritin decrease at 6 months follow-up in the sevelamer hydrochloride group. Increase in C-reactive protein was found in the group of patients treated with calcium carbonate. In conclusion, we found an oxidative state imbalance with increase in LPO and NO oxidants. The activity of the antioxidant enzymes (SOD and TAC) was also found to increase, suggesting a compensatory effect in the face of increase in oxidants. The same phenomenon was observed with increase in the oxidative damage marker to DNA and the increase in the DNA repair enzyme, suggesting a compensatory effect. Pro-inflammatory cytokines were predominantly downregulated by TNF-α in the group that ingested sevelamer hydrochloride in the final determination at 6 months of follow-up. Serum ferritin levels decreased significantly at the end of follow-up in patients on HD in the sevelamer hydrochloride group. The management of hyperphosphatemia with sevelamer hydrochloride appears to have obvious anti-inflammatory and antioxidant benefits.